2011
DOI: 10.1002/clc.20868
|View full text |Cite
|
Sign up to set email alerts
|

Role of CA‐125 in Identification of Right Ventricular Failure in Chronic Obstructive Pulmonary Disease

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a progressive and debilitating disease. Cor pulmonale, characterized by right ventricular (RV) failure, can severely influence prognosis in these patients. Hence, early recognition might be important for tailoring therapy. An old biomarker, CA-125, seems to be associated with the right heart. We aimed to show the relationship between CA-125 levels and RV failure in patients with COPD. Hypothesis: CA-125 might be a useful biomarker in identification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 69 publications
1
18
0
Order By: Relevance
“…D' Aloia et al [4] showed a significant correlation of CA 125 levels with the right atrial and systolic pulmonary artery pressure. In a different study by Yilmaz et al [5], elevated levels of CA 125 reflected right ventricle dysfunction in patients with COPD even before corpulmonale to be evident [5]. Our report adds to the literature a unique case that describe CA 125 elevation in a patient with isolated right heart failure in the setting of rheumatic heart disease [6,7].…”
Section: Discussionsupporting
confidence: 52%
“…D' Aloia et al [4] showed a significant correlation of CA 125 levels with the right atrial and systolic pulmonary artery pressure. In a different study by Yilmaz et al [5], elevated levels of CA 125 reflected right ventricle dysfunction in patients with COPD even before corpulmonale to be evident [5]. Our report adds to the literature a unique case that describe CA 125 elevation in a patient with isolated right heart failure in the setting of rheumatic heart disease [6,7].…”
Section: Discussionsupporting
confidence: 52%
“…MUC16 has been mostly studied in ovarian cancer, but is known to be expressed in normal airway epithelia and submucosal glands (Davies et al, 2007). The blood level of MUC16 in COPD patients was significantly higher than that in control subjects, and directly correlated with systolic pulmonary arterial pressure (Yilmaz et al, 2011). Other than these limited reports, the function of MUC16 in the airways is unknown.…”
Section: Mucus Mucins and Copdmentioning
confidence: 99%
“…Moreover, CA125 levels have been shown to correlate with adverse outcomes in patients with heart failure [14,15]. Recently carried out studies have also reported elevated CA125 levels in patients with coronary heart disease, chronic obstructive pulmonary disease, hypertrophic cardiomyopathy, cardiac angiosarcoma, infective perimyocarditis, and atrial fibrillation [5][6][7][8][9]. However, in stark contrast, few data have been published on the association between serum CA125 levels and the clinical outcomes of patients who have undergone OPCAB.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, normal cells from different tissues derived from coelomic epithelium, including the pericardium, pleura, and peritoneum, can produce CA125 in response to mechanical stress and inflammatory stimuli [2][3][4]. Recent studies have shown that increased CA125 levels play a prognostic role in cardiopulmonary disorders such as coronary heart disease, chronic obstructive pulmonary disease, hypertrophic cardiomyopathy, cardiac angiosarcoma, infective perimyocarditis, and atrial fibrillation [5][6][7][8][9]. However, the relationship between elevated CA125 levels and clinical outcomes after off-pump coronary artery bypass grafting (OPCAB) has not been reported.…”
Section: Introductionmentioning
confidence: 99%